2002
DOI: 10.1007/bf02850269
|View full text |Cite
|
Sign up to set email alerts
|

Fixed combinations of delapril plus indapamide vs fosinopril plus hydrochlorothiazide in mild to moderate essential hypertension

Abstract: This 12-week randomized, parallel-group, multicenter study compared fixed combinations of delapril (D) 30 mg plus indapamide (I) 2.5 mg and fosinopril (F) 20 mg plus hydrochlorothiazide (H) 12.5 mg in 171 adult patients with mild to moderate essential hypertension. After a 2-week placebo run-in, sitting and standing systolic (SBP) and diastolic blood pressure (DBP) was measured by conventional sphygmomanometry. The primary efficacy endpoint was the percentage of normalized (sitting DBP < or =90 mm Hg) and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Several such trials have been reported in the past few years [5][6][7][8]. The same mechanism is true for ARB + diuretic combinations [9][10][11][12].…”
Section: Angiotensin-inhibiting Drugs and Diureticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Several such trials have been reported in the past few years [5][6][7][8]. The same mechanism is true for ARB + diuretic combinations [9][10][11][12].…”
Section: Angiotensin-inhibiting Drugs and Diureticsmentioning
confidence: 94%
“…Much has been written in recent years about the advantages and disadvantages of using fixed drug combinations [5][6][7][8][9][10][11]13,15,[17][18][19][20][21][22][23][24][25][26][27][28][29]. There are also arguments relevant to the proper timing of instituting a chosen fixed combination-that is, as first choice upon initiation of drug therapy or upon reaching the BP goal, after which no further changes are likely to be needed [31][32][33][34][35].…”
Section: Fixed Drug Combinationsmentioning
confidence: 99%
“…failure have been studied mainly in adults, but these are assumed Reported pediatric experience with ACE inhibitors is limited to to be applicable in pediatric heart failure. captopril, enalapril, and cilazapril, [13] although more than ten other In heart failure, cardiac systemic output is decreased [32,33] be-ACE inhibitors have been developed and used in adults, including cause of either increased cardiac load, such as a large left-to-right alacepril, [45] benazepril, [46] delapril, [47] fosinopril, [47,48] imishunt resulting from a large ventricular septal defect in infancy, [34] dapril, [49] lisinopril, [50] perindopril, [51] quinapril, [52] ramipril, [53] or myocardial dysfunction, such as dilated cardiomyopathy temocapril, [54] and trandolapril. [55] (DCM).…”
mentioning
confidence: 99%
“…Since outcome measures were similar for all four studies27–30 included in the meta-analysis, we considered the definitions used in each study as follows: normalized patients were defined as showing a reduction in sitting DBP ≤ 90 mmHg at the 4-week visit27,29 or at the end of the 12-week period of treatment 28,30. Responder patients were defined as: (a) showing a reduction in sitting DBP of 15 mmHg after 1 month of treatment, compared to baseline values;27 (b) showing a reduction in sitting DBP of 10 mmHg compared to baseline values or DBP ≤ 90 mmHg after 12 weeks of treatment;28,30 or (c) demonstrating a reduction in sitting DBP of 10 mmHg from baseline after 1 month of treatment 29.…”
Section: Methodsmentioning
confidence: 99%
“…Responder patients were defined as: (a) showing a reduction in sitting DBP of 15 mmHg after 1 month of treatment, compared to baseline values;27 (b) showing a reduction in sitting DBP of 10 mmHg compared to baseline values or DBP ≤ 90 mmHg after 12 weeks of treatment;28,30 or (c) demonstrating a reduction in sitting DBP of 10 mmHg from baseline after 1 month of treatment 29. Leonetti27 reported two definitions of patient responders: (a) patients with reduction in sitting DBP of 15 mmHg and (b) a second, wider definition, which also included the definition of normalized patients.…”
Section: Methodsmentioning
confidence: 99%